Improving ICT for ODL in the UNISA Department of Public Administration - Naidoo, Goonasagree (Mediterranean Journal of Social Sciences, 2012)
The University of South Africa (UNISA) is a comprehensive open and distance learning(ODL) institution that aims to be the premier online teaching and eLearning institution ofchoice. This article presents a case study of the Department Public Administration inUNISA with regard for the expansion of ODL practices to improve online teaching andeLearning. The purpose of this article is firstly to recommend that the teaching and learningmethods presently used by the Department of Public Administration (UNISA) should becombined with more interactive technology-enriched teaching and learning methodologiesso that the department can â€œbe ahead of the gameâ€ when it comes to online teaching andeLearning.. The significance of this study is to improve Public Administration teaching andlearning by the Department of Public Administration (UNISA) through creating a virtualstudy environment and in ensuring the department becomes a fully fourth and fifthgeneration ODL provider. This includes an explanation of the blended use of Informationand Communication Technology (ICT) tools such as interactive satellite-based platforms,web-based management system and social networks, as mechanisms for improving onlineteaching and eLearning methodologies in Public Administration.